Development of Line Layout Models to Increase Student Involvement in Physical Education, Sports, and Health’s Learning at The Sports Court - Iqbal Albani; Zihan Novita Sari; Abdul Hadi Setyo Pramono; Tya Clarita (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The study aimed to develop an innovative line layout model to enhance student involvement and motivation in Physical Education, Sports, and Health (PJOK) classes. Utilizing the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—the research included field and literature studies to assess current layout strategies in PJOK sessions, identifying that a lack of variety in layout contributes to low engagement. This developmental research focused on creating a row layout model specifically for PJOK conducted outdoors, prioritizing active learning and student interaction. At the analysis stage, interviews and observations at SMAN 4 Malang revealed a demand for engaging, adaptable layouts. The design phase involved creating materials and visual aids to support various layout models that promote physical activity, collaboration, and effective teacher supervision. Experts validated the product on aspects of accuracy, convenience, appeal, and feasibility, achieving a high validity index of 0.92. Results indicate that the layout model is both practical and potentially effective for increasing student motivation and participation, though further application research is necessary to evaluate its direct impact on PJOK learning outcomes